2019
DOI: 10.1155/2019/9168153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome in Patients with Coronary Slow Flow Phenomenon

Abstract: The coronary slow flow phenomenon (CSFP) is a poorly recognized clinical entity characterized by delayed distal vessel opacification in the absence of epicardial coronary stenosis and presently lack of specific data on the clinical profile and outcome. We investigated a cohort of 429 patients who fulfilled the criteria for CSFP to explore the clinical feature, outcome, and risk factor of prognosis. Two teams (clinical center and core lab) were blind to patient data for the assessment of coronary angiograph usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…55% of the study population was male but there was no relation established between sex and CSFP in this paper. Although previous observational studies have concluded that these patients have good prognosis, Zhu et al revealed that an age above 50 and dyslipidemia are associated with adverse outcome in patients with CSF [11]. The mean age of the CSF group was 53 and the groups differed in terms of LDL and total cholesterol levels in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…55% of the study population was male but there was no relation established between sex and CSFP in this paper. Although previous observational studies have concluded that these patients have good prognosis, Zhu et al revealed that an age above 50 and dyslipidemia are associated with adverse outcome in patients with CSF [11]. The mean age of the CSF group was 53 and the groups differed in terms of LDL and total cholesterol levels in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…CSF is a significant angiographic complication (15)(16)(17) that is usually characterized by an overlap between the injection of contrast medium in a coronary angiography and when this dye passes through the coronary artery (18). CSF is a common disease (19) that is more easily recognized in patients with acute coronary syndrome (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical Implications. The SCFph is not without clinical consequences, as reported [ 38 ]. Angina is the major clinical complaint, confirmed in our SCFph series.…”
Section: Discussionmentioning
confidence: 56%